A Technology Development Matrix for Carbon Capture: Technology Status and R&D Gap Assessment - Baker, Ryan; Alizadeh Sahraei, Ommolbanin; Dal-Cin, Mauro Mario; Bensebaa, Farid (Frontiers in Energy Research, 2022)
Numerous carbon capture, utilization, and storage (CCUS) technologies are under development to reduce CO2 emissions. To evaluate the status of a CCUS technology under development and identify potential gaps for further advancement, we have established a new technology assessment framework, and are developing a decision-making tool, the technology development matrix (TDM), starting with available carbon capture technology (CCT) data. TDM is a data inventory system, and screening tool. As a screening tool, it can be used for resource allocation decisions in research, development, and deployment (RD&D) by academia, government, and industry. As an inventory system, it shares data with techno-economic analysis (TEA) and life cycle assessment (LCA) tools. Using available data this TDM framework has been demonstrated on amine based (monoethanolamine) absorption post-combustion CO2 capture, for pulverized coal power plant flue gas, as the best available technology for the sake of comparison. Three groups of promising post-combustion CCTs under development are presented as Alternative Technology (Alt Tech) case studies, including membrane, solid adsorption, and Calcium based chemical looping. Preliminary analysis using available data enabled technology benchmarking and highlighting knowledge, data, and technology gaps, all providing potential future RD&D focus.